Moderators for race-based couple discrimination and problem-solving for Black-White couples: the role of ethnic identity and self-esteem - Patel, Sunny (Kansas State University, 2020)
Interracial marriages continue to lack support in the U.S. society despite the rise in the number of persons entering such unions. Understanding how Black-White couples cope with race-based couple discrimination within their relationships can help therapists build couple resilience. Informed by the minority stress model, this study examined the relationship between race-based couple discrimination and problem-solving in 178 Black-White marriages. The study further examined how protective factors --ethnic identity and self-esteem -- may buffer the effects of discrimination on problem-solving. Results indicated that interracial couples experience discrimination. As expected, an initial overall regression analysis found couple discrimination negatively linked to problem-solving. However, closer examination across race and gender revealed that couple discrimination was negatively associated with problem-solving for Black wives and White husbands. This relationship was moderated by ethnic identity for Black wives and self-esteem for White wives. Although Black husbands in this study reported the highest levels of couple discrimination and use of problem-solving, results did not indicate a significant relationship between the two. Implications for clinical work and future research are discussed.
Keywords: Black-White couples; Self-esteem; Ethnic identity; interracial; marriages; discrimination; problem-solving; race-based couple discrimination; Black husbands; White husbands; White wives; Black Wives